IMPLEMENTATION OF CHARACTER EDUCATION IN STUDENTS THROUGH INTEGRATION OF CHARACTER EDUCATION IN EDUCATION OF SCIENCE OF SOCIAL KNOWLEDGE IN HIGHER EDUCATION - Nasith, Ali (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Character education is applied in the education world to create a dignified young generation in order to educate the nation's life and aims to be a believer and devout believer, a virtuous, healthy, knowledgeable, competent, creative, independent, and citizen democratic and responsible. The value of the character education that must be developed in college includes religious; honest; tolerance; discipline; hard work; creative; independent; democratic; curiosity; national spirit; love of homeland; appreciate achievement; friendly / communicative; peace love; likes to read; care about the environment; social care; and responsibility. Integration of character education in IPS learning in higher education can be done through learning planning, including syllabus, Lecture Event Unit (SAP), and teaching materials; the implementation of learning, including preliminary activities, core activities, and closing; evaluation of learning. This corresponds to the results of observation and experience on campus researchers showing that most students when new lectures begin to not appreciate lecturers who provide material but are more busy with their own activities such as playing HP to update status on facebook or chat with friends. Or take a lecture because she does not like the lecturer by hanging out at the mall. Not to mention "cheat" during the exam because they do not master the material, or copy and paste the work of a friend.